Musical Education, Child And Adolescent Development, And Human Rights Perspective: A Bibliographic Review - Arguedas-Quesada, Consuelo (2015)
This document emerges as a result of the bibliographic review performed by the author in order to achieve her Master degree in Human Rights of Children and Adolescents, for the Graduate Program in Social Work at the University of Costa Rica.  For that reason, the article reviews several studies performed by the time of the investigation based on the national and international background knowledge. The following topics are discussed: pedagogic musical practice, musical education and school curriculum, music and Down’ syndrome, multiple intelligence and integral development, art expression and human development, rights and art expression, and Human Rights for disabled people. The objective of this study is to compare and contrast those subjects, allowing the linking of Human Rights to musical education and its practice in disable people or not, with the objective of sharing the results with people interested in this area. As part of the conclusions this search shows that in Costa Rica there are no jobs related to Human Rights and musical education for Children and Adolescents, and most music works are focused on the multiple intelligences.